EFEKTIVITAS SEDIAAN KRIM EKSTRAK UBI UNGU (Ipomoea batatas Poir) TERHADAP Staphylococcus aureus - Munifah Wahyuddin; Munadiah Wahyuddin; Nurlia Naim; Nevyanti A.P (Jurnal Kesehatan, 2019)
This study aims to determine the effectiveness of cream preparations from purple yam extract (Ipomoea batatas Poir) in inhibiting the growth of Staphylococcus aureus and to determine the concentration of purple sweet potato extract cream preparations (Ipomoea batatas Poir) which effectively inhibit Staphylococcus aureus. The method used in extraction was extracted using the percolation method. The resulting extract was then formulated in the form of cream preparations with varying concentrations of 10%, 15%, 20% and negative controls. Cream tests performed include organoleptic tests, pH, spreadability and type of cream. In testing the effectiveness of Staphylococcus aureus, using the wells method with Nutrient agar (NA) as a medium. Incubated for 24 hours then measuring the zone of inhibition produced in the medium. The results of research conducted for organoleptic (color and odor) tests with concentrations of 10%, 15%, and 20% are dark purple and have a characteristic odor of cream while negative controls are clear and odorless. In the pH test with concentrations of 10%, 15%, 20% ie 6.5 and negative control 6.4. In testing the spread of power with a concentration of 10%, 15% 20% and negative control respectively were 4.9cm, 5cm, 5.3cm and 4.5cm. In testing cream types with concentrations of 10%, 15%, 20% and negative controls are types of oil in water. For effectiveness testing, the most effective inhibition zone was obtained to inhibit Staphylococcus aureus with a concentration of 20% of 16.63 mm.